2022
DOI: 10.3389/fcimb.2022.804011
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Alpha Induces Cellular Autophagy and Modulates Hepatitis B Virus Replication

Abstract: Hepatitis B virus (HBV) infection causes acute and chronic liver diseases, including severe hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC). Interferon alpha 2a (IFNα-2a) is commonly used for treating chronic HBV infection. However, its efficacy remains relatively low. Yet, the immunological and molecular mechanisms for successful IFNα-2a treatment remain elusive. One issue is whether the application of increasing IFNα doses may modulate cellular processes and HBV replication in hepatic cells. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Our findings suggested that Tapasin‐shRNA transfection into DCs might activate mTOR and inhibit autophagy in CD8 + T cells to consequently weaken specific HBV immune responses. It is notable that IFN‐α2a treatment's downregulation of AKT/mTOR signaling augments autophagosome production by restraining autophagic degradation 22 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggested that Tapasin‐shRNA transfection into DCs might activate mTOR and inhibit autophagy in CD8 + T cells to consequently weaken specific HBV immune responses. It is notable that IFN‐α2a treatment's downregulation of AKT/mTOR signaling augments autophagosome production by restraining autophagic degradation 22 …”
Section: Discussionmentioning
confidence: 99%
“…In reverse, some viruses require autophagic components for their own survival and replication, as their replication can be abolished by autophagy inhibitors ( Choi et al., 2018 ). In our published work, we demonstrated that IFN-α triggered autophagy and promoted HBV replication in an in-vitro study ( Li J. et al., 2022 ). Some viruses strategically exploit the early stages of autophagy and antagonize autophagosome maturation to prevent degradation ( Kyei et al., 2009 ; Lin et al., 2020a ), utilize autophagy-related lipid metabolism for efficient replication ( Heaton and Randall, 2010 ; Kim et al., 2017 ), while some even exploit autophagy as an assembly platform and release pathway ( Chu et al., 2022 ).…”
Section: Autophagy and Viral Infectionmentioning
confidence: 95%
“…Research found a correlation between type 1 interferons and autophagy [24,29]. Type 1 interferon is an inducer of autophagy [30][31][32]. Interferon regulatory factor 1 (IRF1), which can activate interferon beta, is also related in autophagy [33].…”
Section: Th3 Immune Response and Its Relation To Autophagic Deathmentioning
confidence: 99%